The Prevalence of Metabolic Syndrome and Hypertriglyceridemic Waist Based on Sociodemographic Variables and Healthy Habits in Healthcare Workers: A Retrospective Study - Pedro Javier Tárraga Marcos; Ángel Arturo López-González; Emilio Martínez-Almoyna Rifá; Hernán Paublini Oliveira; Cristina Martorell Sánchez; Pedro Juan Tárraga López; José Ignacio Ramírez-Manent (Life)
Introduction: Metabolic syndrome (MetS) and hypertriglyceridemic waist (HTW) are two multifactorial pathological conditions that have been increasing in prevalence worldwide. The objective of this study was to evaluate how various sociodemographic variables and healthy habits are associated with the presence or absence of MetS and HTW. Methodology: This study employed a mixed-methods approach, consisting of a retrospective longitudinal study and a cross-sectional descriptive study, analyzing 44,939 healthcare workers with MS and HTW across four professional categories to evaluate the relationship between age, sex, smoking, physical activity, and adherence to the Mediterranean diet using three diagnostic criteria. Descriptive analysis included categorical and quantitative variables, which were assessed through frequencies, Student’s t-test, chi-square, and binary logistic regression models. Logistic regression and Cohen’s kappa were used to evaluate associations and concordances. Age, sex, and lack of physical activity showed the strongest associations with MetS (OR: 2.65–2.84). The results highlight the importance of physical activity and other factors in metabolic prevention. Results: Age, sex, and physical activity were the variables most strongly associated with MetS and HTW across the three evaluated diagnostic criteria. The odds ratios revealed significant values: age (9.07–13.71 for MetS and 13.42 for HTW), sex (2.82–3.31 for MetS and 3.72 for HTW), and physical activity (2.65–2.84 for MetS and 2.40 for HTW). Conclusions: The risk of developing MetS and HTW among healthcare personnel is influenced by lifestyle habits, sex, and age, with the highest ORs observed in nursing assistants and orderlies. Future research that delves deeper into the causal relationship between lifestyle factors and the severity of MetS and HTW in healthcare personnel will improve understanding and facilitate the development of preventive activities to reduce their incidence.